The conjoint conceptualization and negotiation of national cultures : qualitative study of discursive culture-concepts, their function and their relation to stereotypes - Bennung, Martin Pablo (2015)
The study of stereotypes and stereotyping is as complex and multi-facetted as the social phenomenon itself. From being seen as an erroneous and over-generalizing image in the mind of individuals, to the current perspective that stereotypes have an individual and a social level, are shaped by long-term and short-term contextual factors, and are used for certain purposes, managed and negotiated, stereotypes have been acknowledged as a topic which cannot be studied within one academic discipline alone. This study looks into stereotype use and management during in-group discourse about other national cultures. The data consists of three focus groups consisting of Finnish students who talk about their attitudes towards other cultures. While the study is theoretically informed by the different fields interested in the phenomenon, it does not adapt or tend towards any single theoretical position. The analysis reveals that the group functions of stereotypes as laid out in Social Identity Theory can be observed in talk, but in a significantly more varied and complex way than expected. The nature of a short-term conversation as driven by stake, functions, context and individual factors, gradually turns out to be incompatible with any stereotype definition. The results argue for a separation between stereotypes as defined in social psychological literature, and the conjoint creation of a discursive culture-concept as a construct that only exists in the moment of the conversation. We finally address the complex relation between stereotypes and concepts.